2010
DOI: 10.3233/ch-2010-1278
|View full text |Cite
|
Sign up to set email alerts
|

No apparent correlation between Behçet’s disease and oxidative stress disturbance

Abstract: Behçet's disease (BD) is a chronic, progressive and inflammatory multisystemic disease, that significantly affects the cardiovascular system. Oxidative stress (OS) is a disturbance in oxidant/antioxidant balance in favor of oxidants. The OS that increases acutely and chronically due to the inflammatory process plays an important role in the pathogenesis of the cardiovascular system effects of the disease by causing endothelial dysfunction in vascular structures. The aim of our study was to investigate the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…So, they are prone to oxidative damage, which reduces cell survival and induces the release of juvenile erythrocytes into blood circulation. There are several studies available in the literature regarding this subject [32][33][34], in which oxidative response was found to be disrupted in both active and inactive BD patients.…”
Section: Discussionmentioning
confidence: 99%
“…So, they are prone to oxidative damage, which reduces cell survival and induces the release of juvenile erythrocytes into blood circulation. There are several studies available in the literature regarding this subject [32][33][34], in which oxidative response was found to be disrupted in both active and inactive BD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress reflects an imbalance between the systemic manifestation of reactive oxygen species (ROS) and the ability of the body to readily detoxify reactive intermediates or to repair the resulting damage (12). Numerous studies have demonstrated that oxidative stress is an important factor underlying abnormal cardiovascular system structure (13)(14)(15). In addition, various cardiovascular diseases, including hypertension, atherosclerosis, myocardial ischemia, ischemia-reperfusion injury, myocardial hypertrophy and heart failure, are associated with an increase in ROS generation.…”
Section: Introductionmentioning
confidence: 99%